Safety and efficacy of thermal ablation for cervical metastatic lymph nodes in papillary thyroid carcinoma: A systematic review and meta-analysis - Tang, Wanqing; Tang, Xiuyun; Jiang, Danni; Zhang, Xiaojuan; Wang, Rongling; Niu, Xiaoyan; Zang, Yichen; Zhang, Mingzhu; Wang, Xinya; Zhao, Cheng (Frontiers in Endocrinology, 2022)
Background: To evaluate the safety and efficacy of radiofrequency ablation (RFA), microwave ablation (MWA), and laser ablation (LA) for the treatment of cervical metastatic lymph nodes (CMLNs) of papillary thyroid carcinoma (PTC). Methods: The Pubmed, EMBASE, Web of Science, and Cochrane Library databases were searched for studies on the safety and efficacy of thermal ablations (RFA, MWA, and LA) for the treatment of CMLNs of PTC until March 30, 2022. A review of 334 potential papers identified 17 eligible papers including 312 patients. Fixed-effects model or random-effects model was used to evaluate the pooled proportions of VRR, complete disappearance, and recurrence, and pooled estimates of changes in the largest diameter, volume, and serum Tg after ablation. The pooled proportions of overall and major complications were calculated. Subgroup analysis based on treatment modalities. The heterogeneity among studies was analyzed by using Q statistics and inconsistency index I2. MINORS scale was used to evaluate the quality of the studies. Results: 17 eligible studies were finally identified, including 312 patients and 559 CMLNs. The pooled proportions of VRR, complete disappearance and recurrence of CMLNs were 91.28% [95% confidence interval (CI): 86.60-95.97%], 67.9% [95% CI: 53.1-81.1%] and 7.8% [95%CI: 3.0-14.1%], respectively. The pooled estimates of changes in the largest diameter, volume and serum Tg were 8.12 mm [ 95%CI: 6.78-9.46 mm], 338.75 mm3 [95%CI: 206.85 -470.65 mm3] and 5.96 ng / ml [ 95%CI: 3.68-8.24 ng/ml], respectively. The pooled proportions of overall and major complications were 2.9% [95%CI: 0.3-7.1%] and 0.3% [95%CI: 0-1.9%], respectively. Significant between-study heterogeneity was observed for complete disappearance, VRR, recurrence, overall complications, and changes in the largest diameter, volume, and serum Tg (P < 0.001). Subgroup analysis showed heterogeneity of the VRR among the treatment modality (I2 range: 84.4-100%). The VRR of MWA was the highest (97.97%), followed by RFA (95.57%) and LA (84.46%) (P < 0.001). Conclusion: All thermal ablations were safe and effective for the treatment of CMLNs of PTC. However, each treatment had significant heterogeneity in VRR. Compared with RFA and MWA, LA was less effective in reducing the volume of CMLNs of PTC.